Non-state actor dynamics in international law : from law-takers to law-makers from law-takers to law-makers - Noortmann, Math.; Ryngaert, Cedric (Farnham, Surrey, England ; Burlington, Vt. : Ashgate, 2010)
Non-state actors have always been treated with ambivalence in the works of international law. While their empirical existence is widely acknowledged and their impact and influence uncontested, non-state actors are still not in the centre of international legal research. The idea that non-state actors are not law-makers, however, stands in sharp contrast with the growing notion of non-state actors as law-takers. This book examines the position of non-state actors in international law as law-makers and law-takers and questions whether these different positions can or should be separated from each other. Each contribution reveals both the political and normative aspects of the question as well as the positivistic possibilities and constraints to accommodate non-state actors as law-takers and law-makers in the contemporary international legal system. Altogether, each expert reveals that the position of non-state actors in international law is not a fixed one but changes with the functional and theoretical perspectives of the observer. Non-State Actor Dynamics in International Law is a welcomed addition to an under researched field of legal study. An indispensable read to scholars and policy makers wishing to gain new insights into general discourse on non-state actors in international law and the process of norm formation in the international realm. -- Back cover.
Introduction : Non-state actors : international law's problematic case / Math Noortmann & Cedric Ryngaert -- Multinational enterprises as actors in international law : creating "soft law" obligations and "hard law" rights / Peter Muchlinski -- The impact of non-state actors on the international law regime of corporate social responsibility : blessing or curse? / Leyla Davarnejad -- Imposing international duties on non-state actors and the legitimacy of international law / Cedric Ryngaert -- Non-state actors and the international rule of law : revisiting the "realist theory" of international legal personality / Janne E. Nijman -- Observations on the desirability of an enhanced international legal status of the non-state actor / Noemi Gal-Or -- Understanding non-state actors in the contemporary world society transcending the international, mainstreaming the transnational, or bringing the participants back in? / Math Noortmann -- International law-making by non-state actors : changing the model or putting the phenomenon into perspective? / Jean d'Aspremont -- Non-state actors : law-takers or law-makers? : is that the question? / Math Noortmann & Cedric Ryngaert.
Includes bibliographical references and index.
Keywords: Non-state actors (International relations); Non-governmental organizations; NGOs; ONG